Psychological and Emotional State of Students and Residents in Medical Universities - D. P. Derbenev; E. N. Sergeeva; A. A. Rodionov (Здоровье мегаполиса, 2025)
The purpose of the study was to assess the psychological and emotional state of students and residents in medical universities in relation to their sex, professional stage, and training special-ty. Materials and methods. The study included 1,007 medical students undergoing specialty and residency programs. The study assessed the psychological and emotional state of students and res-idents in medical university based on anxiety and depression levels. The study applied validated psychological, sociological, and statistical methods for data collection, processing, and subsequent analysis. Results. The general psychological and emotional state of students and residents of medi-cal universities is relatively prosperous and characterized by a majority of individuals having no signs of anxiety or depression. Female students tend to have higher anxiety levels. The study de-picted a tendency toward depression level increase from the first-year specialists to the residents. The level of psychological and emotional well-being of students (specialists and residency gradu-ates) majoring in pediatrics is noticeably higher than in comparable groups of dentistry and general medicine.